A Robust Harvest: Strategic Choices For Agricultural And Rural Development In Vietnam - Ian Coxhead; Kim N.B. Ninh; Vu Thi Thao; Nguyen Thi Phuong Hoa; Ian Coxhead; Kim N.B. Ninh; Vu Thi Thao; Nguyen Thi Phuong Hoa
This report was commissioned by the Development Strategy Institute (DSI) of the Ministry of Planning and Investment and UNDP. The report contains views of the consultant team and does not necessarily refl ect the offi cial views or positions of DSI or UNDP.